Implementasi Kebijakan Program Jawa Timur Pemberdayaan Usaha Perempuan (Jatim Puspa) - Lorenza, Yohanna Christiani; Nawangsari, Ertien Rining (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2023)
The Jatim Puspa Program is an effort made by the East Java Provincial Government to increase the income of people affected by COVID-19 with a target for people who are at the lowest 8-12% welfare level. Batu City is the only city in East Java Province that receives assistance from the Jatim Puspa Program targeting 123 Beneficiary Families (KPM) spread across 6 villages, one of which is Gunungsari Village. The aim of this research is to analyze and describe the implementation of the East Java Puspa Program policy in Gunungsari Village, Batu City. The method used in this research is descriptive qualitative. The data collection techniques used were interviews, observation and documentation. The data analysis model consists of data collection, data presentation, data condensation, and drawing conclusions. The research results show that the Policy Content and Policy Context in the Jatim Puspa Program in Gunungsari Village, Batu City can be said to have been successful, but there are still targets that need to be optimized again. However, overall the implementation policy of the Jatim Puspa Program in Gunungsari Village, Batu City has been carried out well.